TINJAUAN HUKUM PENDAFTARAN HAK TANGGUNGAN SECARA ELEKTRONIK (HT-el) SEBAGAI PEMENUHAN ASAS PUBLICITEIT - Winarsasi, Putri Ayi (PMIH Untag Semarang, 2022)
Technology development is very influential in many aspects, including credit agreement as the principal agreement that followed by the accesoir agreement or guarantee agreement. Guarantee agreement is aimed for immovable objects, such as land or building, which written on Law number 4/1966 on Mortgage Rights of Land and other related objects or known as Undang-Undang Hak Tanggungan (UUHT)/ Mortgage Law. However, the registration of mortgage rights which done manually is still having some obstacles, such as the long-time duration, slow bureaucracy, and others. Therefore, it is needed to use information technology to make the mortgage service procedure can be integrated electronically, thus it will become effective and efficient. The Minister of Agrarian Affairs and Spatial Planning (APR) or Head of National Land Agency (BPN) has issued a Regulation of Agrarian Affairs and Spatial Planning/National Lang Agency number 9/2019 about electronically integrated mortgage service since June 21st 2019. This regulation is related to the Regulation number 3/2019 on the use of electronic system and Regulation number 7/2019 on transformation of certificate form. The issuance of these regulations is one of the way to handle the mortgage registration service. It is hoped it can facilitate people to get the service. The electronic registration is also considered as appropriate service to the situation of covid-19 pandemic nowadays.